Upaya penambahan pendapatan keluarga dengan budidaya ikan teknologi sederhana di Kelurahan Binawidya Kecamatan Binawidya Pekanbaru - Iskandar Putra; Rusliadi Rusliadi; Romie Jhonnerie; T. Ersti Yulika Sari (Unri Conference Series: Community Engagement, 2021)
The Covid-19 outbreak has a global impact, especially in terms of the community's economy, so that those affected by this outbreak find it difficult to finance their daily needs, therefore efforts are needed to increase people's income. One technology that can be applied is the cultivation of fish in tanks with vegetables (aquaponics). The purpose of this activity is to provide knowledge and skills about the cultivation of catfish (Clarias gariepinus) with aquaponics technology of the bucket fish farming system which can ultimately be used as additional income, besides that it is hoped that this activity can be used as an example in updating/information in the field of aquaculture. This socialization activity was carried out in the "Usaha Mandiri" Group of Binawidya Village, Binawidya District, Pekanbaru in June-November 2021. The results achieved in this activity were an increase in the skills knowledge of the training participants, namely the result of evaluating the level of community knowledge about water source technology with the following categories: Do not understand 10% and understand 90%, want to try 60%, the results of observations on the growth of catfish with an average weight of 119,00-127,00 g/indv. and 90% survival rate.